METHODOLOGICAL ASPECTS OF THE RESIDUAL STRENGTH ESTIMATION OF THE DAMAGED HULL STRUCTURES - Roman A. Pochinkov; Boris V. Sobol (Advanced Engineering Research, 2010)
Methodological aspects of forecasting fatigue fracture propagation in various constructive elements of the sea transport are investigated. General methodology for such calculations, and conceptual forecast algorithm of crack growth in the ship hull structures with numerical methods of strength analysis are offered.